ANALISIS KEMAMPUAN MAHASISWA PGSD SEMESTER I DALAM MENYELESAIKAN SOAL-SOAL MATA KULIAH KONSEP DASAR IPA I POKOK BAHASAN SISTEM PERNAPASAN DENGAN MENGGUNAKAN METODE DEMONSTRASI - Ridwan Jusuf (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2015)
This research intend to know PGSD college student ability in first semester to solve sains I college base concepts respiratory system subject by applying demonstration method. Observational type that have been used in observational descriptive which is a research that to know college student ability in solve sains I college base concepts respiratory system subjects by applying demonstration method, the subject of this research is student college in education learns elementary school major (PGSD) first semester that have been contracted to Sains Base Concept college with total 55 college students. The tech that have been use in this research is essay. Essays can be use to know college student ability in solve sains I college base concepts respiratory system subjects by applying demonstration method to forms essays that total 10 problems with 100 maximum score. The data that have been acquired analyzed by use of statistic descriptive. Have been know from analizyed ability college student can do sains I ability problem base concept colleges respiratory system discussion subjects by applying demonstration method, have gotten by mean's data (M ) = 75 by standard deviation (SD) = 5,9, there are college student ability solve sains I college problems base concepts respiratory system subjects by applying demonstration method, there are college student has ability too solve problems with varying level which is pretty good 6 person (11%), well 18 person (33%), passably 23 person (42%), adverse 6 person (11%) and so adverse 2 person (4%) .